Biopolímeros ferti-liberadores: uma proposta de recipiente para o cultivo de mudas de antúrios - Teixeira, Rayan Nascimento (Universidade Federal de São Carlos, 2024)
The improper management of plastic waste in agriculture, coupled with the high demand for soil fertilization, has resulted in significant adverse environmental impacts. Efforts to address these issues involve the development of materials that efficiently utilize fertilizers while minimizing waste generation. This study proposes the formulation and optimization of a film incorporating natural polymers such as Alginate (Alg), Carrageenan (Kc), and nanofibrillated cellulose (CNF), supplemented with macro and micronutrients. The fertilizer concentrations vary at 0.4 dS m-1, 0.8 dS m-1, 1.2 dS m-1, and 1.6 dS m-1, aligning with nutritional recommendations for anthurium cultivation. The primary objectives are to assess the thermal, structural, and morphological properties of the film and to evaluate its biodegradation and performance as a plant propagation container in the field. Films were produced through casting, and their nutrient release and biodegradation properties were systematically analyzed in relation to the chemical structure. Laboratory-based biodegradation assessments utilized the Bartha and Pramer respirometric method, while field-based fertilizer release was conducted within an agricultural greenhouse through chemical analysis of plant tissue and substrate. The efficiency of nutrient absorption was gauged through biometric analyses of anthurium seedlings in the field, measuring height, diameter of the largest leaf, number of leaves, fresh and dry mass at 30-day intervals (30, 60, and 90 days). Statistical treatment involved analysis of variance (ANOVA), followed by Tukey tests at a 5% significance level. The results indicate that the highest fertilizer concentration, 1.6 dS m-1, emerged as the optimal treatment based on biometric analyses. In conclusion, the developed material exhibits physical characteristics, including resilience and biodegradability, making it suitable for storing and efficiently providing fertilizers. This innovation represents a valuable contribution to seedling production in agriculture, addressing environmental concerns associated with plastic waste.
Ferti-releasing biopolymers: a proposal for a container for growing anthurium seedlings
Keywords: Agricultura sustentável; Materiais biodegradáveis; Fertilizantes; Propagação vegetal.; Sustainable agriculture; Biodegradable materials; Fertilizers; Plant propagation.; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO